The Influence of Shape Parameters on Unidirectional Drug Release from 3D Printed Implants and Prediction of Release from Implants with Individualized Shapes - Vanessa Domsta; Christin Hänsch; Stine Lenz; Ziwen Gao; Farnaz Matin-Mann; Verena Scheper; Thomas Lenarz; Anne Seidlitz (MDPI AG, 2023)
The local treatment of diseases by drug-eluting implants is a promising tool to enable successful therapy under potentially reduced systemic side effects. Especially, the highly flexible manufacturing technique of 3D printing provides the opportunity for the individualization of implant shapes adapted to the patient-specific anatomy. It can be assumed that variations in shape can strongly affect the released amounts of drug per time. This influence was investigated by performing drug release studies with model implants of different dimensions. For this purpose, bilayered model implants in a simplified geometrical shape in form of bilayered hollow cylinders were developed. The drug-loaded abluminal part consisted of a suitable polymer ratio of Eudragit® RS and RL, while the drug-free luminal part composed of polylactic acid served as a diffusion barrier. Implants with different heights and wall thicknesses were produced using an optimized 3D printing process, and drug release was determined in vitro. The area-to-volume ratio was identified as an important parameter influencing the fractional drug release from the implants. Based on the obtained results drug release from 3D printed implants with individual shapes exemplarily adapted to the frontal neo-ostial anatomy of three different patients was predicted and also tested in an independent set of experiments. The similarity of predicted and tested release profiles indicates the predictability of drug release from individualized implants for this particular drug-eluting system and could possibly facilitate the estimation of the performance of customized implants independent of individual in vitro testing of each implant geometry.